Fishery, stock assessment and biology of the senatorial scallop chlamys senatoria (GMELIN, 1791) in Gigantes Islands, Carles, Central Philippines - Morillo-Manalo, Laureen (Miagao, Iloilo University of the Philippines Visayas, 2017)
The senatorial scallop Chlamys senatoria (Gmelin, 1791) is a commercially import conservation and management strategies, the fishery, stock assessment, ecology and reproductive biology of the species were investigated from June 2013 to May 2014 using fishery-dependent and fishery-independent surveys. The study on fishery aspect (chapter 3) showed that the small-scale scallop fishery has been in existence for three decades with a peak in fishery around 1986-1990. Catch landings were composed of the scallops (C. senatoria, Brachtechlamys vexillum, Annachlamys macassarensis, Decatopecten amiculum, and Decatopecten radula) and spiny oysters Spondylus spp. The scallop with the highest catch was C. senatoria with 32.3 t adductor meat or (44%) of the 72.7 t total scallops catch. Total catch od spondylus spp. was 85.3 t adductor meat. The CPUE of C. senatoria slightlydecreased from June to July and inc reased steadily until it reached a peak in October with the highest CPUE of 2.1 kg meat diver-1 day-1. However, a drastic decline was observed in the month of November with the lowestrecorded value of 0.5 kg meat diver-1 day-1. The decrease in CPUE was possibly due to damage or disturbance in the habitat by strong currents and wave action brought by supertyphoon Haiyan. Majority of the catch were in the size 50-89 mm shell height. The stock assessment study (c hapter 4) showed an overall mean density biomass of 7.7 ind. m-2 and 240.78 g m-2, respectively. A drastic decrease from density and biomass was also recorded in November 2013 in all stations. The computed mean length and weight of C. senatoria were 55.6 mm and32.20g, respectively. the length-weight relationship was W =0.001L2.5. The estimated growth parameters were L 00 = 91.88 mm and K = 0.65 year -1 with a growth performance index (0') of 3.74. The estimated longevity of the species was 4.9 years. The total mortality was computed to be 1.42. The exploitation rate was 0.64 which indicates exploitation of the species beyond optimum. The maximum sustainable yield was 491,179 kg at f-factor 1.1. The recommended value for fMSY is 115 divers. The study on the ecology and reproductive biology (chapter 5)revealed that C. senatoria occurred in rocky and sandy areas at 18-22 m. Temperature, salinity, dissolved oxygen, and pH showed minimal variations over an annual cycle. Aside from C.senatoria, a total of 67 invertebrate species were identified. Epibiontsand endobionts were found growing on scallop shells. The species is dioecious with no apparent externaldimorphism. Five distinct gonad stages were observed : developing, ripe, spawning, redeveloping, and spent. Spawning occurs throughout the year with a major peak fromDecember to February and a minor peak in August. Size at maturity (50% of population is mature) was 57.1 mm and 59.5 mm shell height for males and females. Average fecundity was1.3 x 106 + 5.4 x 105 oocytes female-1 with an average shell height of 70 mm. Results showed that harvesting of scallops should be regulated during the months of peak spawning activities(August and December to February) and sizes should be limited to individuals >59.5 mm shell height.
Dissertation (Doctor of Philosophy in Fisheries) -- Miagao, Iloilo : Institute of Marine Fisheries and Oceanology, College of Fisheries and Ocean Sciences, University of the Philippines Visayas, June 2017.
Keywords: Senatorial scallop; Chlamys senatoria; Stock assessment; Gigantes Island, Carles, Iloilo